Calorie restriction and not glucagon‐like peptide‐1 explains the acute improvement in glucose control after gastric bypass in Type 2 diabetes. Issue 12 (8th October 2016) - Steven, S.; Hollingsworth, K. G.; Small, P. K.; Woodcock, S. A.; Pucci, A.; Aribasala, B.; Al‐Mrabeh, A.; Batterham, R. L.; Taylor, R.
Abstract: Aims: To compare directly the impact of glucagon‐like peptide‐1 secretion on glucose metabolism in individuals with Type 2 diabetes listed for Roux‐en‐Y gastric bypass surgery, randomized to be studied before and 7 days after undergoing Roux‐en‐Y gastric bypass or after following a very‐low‐calorie diet. Methods: A semi‐solid meal test was used to investigate glucose, insulin and glucagon‐like peptide‐1 response. Insulin secretion in response to intravenous glucose and arginine stimulus was measured. Hepatic and pancreatic fat content was quantified using magnetic resonance imaging. Results: The decrease in fat mass was almost identical in the Roux‐en‐Y gastric bypass and the very‐low‐calorie diet groups (3.0±0.3 and 3.0±0.7kg). The early rise in plasma glucose level and in acute insulin secretion were greater after Roux‐en‐Y gastric bypass than after a very‐low‐calorie diet; however, the early rise in glucagon‐like peptide‐1 was disproportionately greater (sevenfold) after Roux‐en‐Y gastric bypass than after a very‐low‐calorie diet. This did not translate into a greater improvement in fasting glucose level or area under the curve for glucose. The reduction in liver fat was greater after Roux‐en‐Y gastric bypass (29.8±3.7 vs 18.6±4.0%) and the relationships between weight loss and reduction in liver fat differed between the Roux‐en‐Y gastric bypass group and the very‐low‐calorie diet group. Conclusions: This study shows that gastroenterostomy increases the rate of nutrient absorption, bringing about a commensurately rapid rise in insulin level; however, there was no association with the large post‐meal rise in glucagon‐like peptide‐1, and post‐meal glucose homeostasis was similar in the Roux‐en‐Y gastric bypass and very‐low‐calorie diet groups. (Clinical trials registry number: ISRCTN11969319.) What's new?: The greater weight loss observed 7 days after Roux‐en‐Y gastric bypass (RYGB) surgery compared with after 7 days of a very‐low‐calorie diet (VLCD) in Type 2 diabetes is attributable to greater loss of lean and water mass. After RYGB, the early and enhanced post‐meal rise in glucose and insulin levels is attributable to rapid absorption through the gastroenterostomy. The increased post‐meal glucagon‐like peptide‐1 secretion specific to RYGB is not accompanied by an improvement in insulin or glucose area under the curve when compared with VLCD. The early improvement in glucose control in Type 2 diabetes after RYGB is not explained by improved β‐cell function. The relationships between weight loss and loss of liver fat 7 days after RYGB and after VLCD appear to differ.